Understanding the impact of healthcare providers’ perspectives on cancer control in rural communities: A qualitative study - Alee Lockman; Mariam Krikorian Atkinson; Keelin McGee; Tenille Oderwald; James McGee (SSM: Qualitative Research in Health)
This study seeks to understand how healthcare providers perceive systemic- and individual-level factors affecting rural patients' access to care and how this information impacts providers’ approach to cancer screening and prevention recommendations. Over a six-month period in 2021, we conducted semi-structured interviews with primary care providers, nurse navigators, and community health workers affiliated with a regional health system to better understand their perceptions of cancer control in rural communities. Thematic analysis was conducted to identify key themes and develop a conceptual framework to describe the pathway between information-gathering and care coordination – as well as how trust affects these relationships. We found that provider beliefs about barriers facing rural patients influence care recommendations and patient interactions. These beliefs and subsequent interactions affect trust between providers and patients, which influences whether rural patients are willing to believe providers, their adherence to care recommendations, and the information patients are willing to share with providers.